Comparative study between monoexponential and biexponential diffusion weighted imaging sequences in multiparametric prostate magnetic resonance imaging - Victor Martins Tonso; Fernando Ide Yamauchi; Thais Caldara Mussi; Eduardo Figueiredo; Ronaldo Hueb Baroni (Einstein (São Paulo))
ABSTRACT Objective: To compare qualitatively and quantitatively, in terms of image quality, a new biexponential diffusion sequence protocol with the standard monoexponential diffusion protocol on multiparametric prostate magnetic resonance imaging. Methods: This study had a prospective data collection and cross-sectional analysis. Between August and November 2017, a total of 70 patients who underwent multiparametric prostate magnetic resonance imaging due to clinical suspicion of prostatic neoplasia were recruited. The images obtained were evaluated by two independent readers regarding subjective/qualitative criteria (six criteria) and objective/quantitative criteria (three criteria), always comparing the monoexponential to biexponential acquisition protocols. The results were compared by statistical analysis (interobserver agreement − Gwet coefficient; analysis of the qualitative variables − Stuart-Maxwell test; and analysis of the quantitative variables − Wilcoxon test). Results: After exclusion of four patients, the final sample consisted of 66 patients. A good/excellent inter observer agreement was stablished for subjective criteria (except in one criteria). For the qualitative analysis the amount of good or excellent evaluations was higher for the monoexponential protocol (except in one category), with evidence of significant differences for three criteria (diffusion weighted imaging global quality; diffusion weighted imaging signal-to-noise ratio; and apparent diffusion coefficient signal-to-noise ratio). For the quantitative data analysis, the monoexponential protocol showed less variability of the anteroposterior diameters, meaning less distortion of the images, and better estimated signal-to-noise ratio. Conclusion: In our data, the quality of the images of the monoexponential standard diffusion sequence was qualitatively and quantitatively superior to those of the biexponential diffusion weighted imaging sequence.